L-Value and Energy Dependence of 0.1-50 keV O +, He +, and H + Ions for CME and CIR Storms Over the Entire Van Allen Probes Era - Pandya, Megha; Veenadhari, B.; Ebihara, Yusuke; Reeves, G. D. (My University, 2022)
Our studies report the first observation of L-value and energy sorted correlation of differential fluxes of 0.1â€“50 keV O +, He +, and H + ions with different geophysical parameters for 29 Coronal Mass Ejected (CME) and 40 Corotating Interaction Region (CIR)-driven geomagnetic storms during the entire Van Allen Probes era. For both solar wind drivers, ions with â‰¥1 keV energies show more variability in response to the solar wind changes, while the lower energy (<1 keV) ions are relatively stable. During the in-storm interval, O + ions show maximum flux enhancement and become further prominent during CME storms. O + ion (â‰¥10 keV) fluxes show good correlation with âˆ’ VswBz, and Sym-H index during CME-driven storms in the L âˆ¼2.5â€“5.5. Apart from this, the average duration of persistence (âŒ©Î”tâŒª) for enhanced fluxes is higher for CIR-driven stormð ´ð ´s with âŸ¨Î”ð ´ð ´ð ‘¡ð ‘¡âŸ©ð ‘‚ð ‘‚+ >âŸ¨Î”ð ´ð ´ð ‘¡ð ‘¡âŸ©ð »ð »ð »ð »+ >âŸ¨Î”ð ‘¡ð ‘¡âŸ©ð »ð »+ at E â‰¤ 50 keV in the L âˆ¼2.5â€“5.5. Moreover, the observed value of âŒ©Î”tâŒªi (where i is O +, H + or He +) increases with the increasing L. We discuss the plausible mechanisms to provide a comprehensive overview of L-values and energy sorted O +, He + and H + ion dynamics for two different categories of solar wind drivers.
Keywords: L-Value; CME; CIR Storms; Van Allen Probes